2008
DOI: 10.1007/s00595-007-3634-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a liver resection for hepatocellular carcinoma in patients with chronic renal failure

Abstract: A hepatectomy for HCC should be considered even for CRF patients with various complications if careful perioperative management and suitable multidisciplinary treatment for recurrent disease are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 22 publications
3
33
2
Order By: Relevance
“… 19 , 20 Some single-center studies showed that end-stage renal disease patients undergoing liver resection did not have higher perioperative mortality compared with patients without end-stage renal disease. 21 23 Our findings revealed that among the factors associated with perioperative mortality because of liver resection, preexisting renal disease was the strongest, which was also in agreement with previous studies of other procedures showing that postoperative acute renal failure significantly impaired the outcomes after major surgery. 24 , 25 This result indicates that when treating patients with renal disease, careful surgical techniques and perioperative management are crucial for lower mortality risk.…”
Section: Discussionsupporting
confidence: 90%
“… 19 , 20 Some single-center studies showed that end-stage renal disease patients undergoing liver resection did not have higher perioperative mortality compared with patients without end-stage renal disease. 21 23 Our findings revealed that among the factors associated with perioperative mortality because of liver resection, preexisting renal disease was the strongest, which was also in agreement with previous studies of other procedures showing that postoperative acute renal failure significantly impaired the outcomes after major surgery. 24 , 25 This result indicates that when treating patients with renal disease, careful surgical techniques and perioperative management are crucial for lower mortality risk.…”
Section: Discussionsupporting
confidence: 90%
“…The survival of patients in this study is comparable to the recent results of liver resection in patients with HCC, in which the cumulative survival rate after surgery was 89.1% at 1 year, 84.4% at 3 years, and 66.0% at 5 years. 29 Incorporating these data with current opinion of the different treatments available, gastric varices that are diffi cult to manage by IVR and patients with relatively good liver function may be better indications for surgical management in portal hypertension. The current series suggests that gastric devascularization and a splenectomy or laparoscopic gastric devascularization and a splenectomy are recommended for portal hypertension at general community hospitals.…”
Section: Discussionmentioning
confidence: 98%
“…In light of these numerous risk factors, the primary focus of the present study was to characterize perioperative outcomes in patients with ESRD submitted to complex hepatopancreaticobiliary procedures. Most of the previous literature on this topic consists of relatively small single‐institution series, which have generally demonstrated the feasibility of performing safe hepatic or pancreatic resection in highly selected patients with renal dysfunction and ESRD . More recently, Squires and colleagues examined the effects of preoperative renal insufficiency on outcomes in a large series of patients undergoing pancreatic resection .…”
Section: Discussionmentioning
confidence: 99%